The impact of practical training program on personal self-development skills / Nurul Izzaty Norrihan and Siti Noor Nabilah Kamarzenin - Norrihan, Nurul Izzaty; Kamarzenin, Siti Noor Nabilah (2022)
Students are required to participate in a practical training programme that has been carefully conceived of, organised, and evaluated might be of great assistance and as an essential component of their educational experience. Practical training programme has an impact towards the students’ personal self-developments skills. By participating in practical training, a student has the opportunity to get considerable professional job experience and they could improve professional skills such as communication, responsibility, and technical competency through the participation in practical training. A research study was conducted to analyse the relationship between practical training and personal self-development among the part 6 students under course code AM228 from the Faculty of Administrative Science and Policy Studies in UiTM Seremban 3, Negeri Sembilan by using online survey. The findings from this survey showed there is a positive view and relationship of students towards practical training and personal self-development. Practical training programme does have an impact on the students’ personal self-development skills.